Creating the visual world of UP dulaang laboratoryo's makinal, Eljay Castro Deldoc's filipino adaptation of machinal by Sophie Treadwell through Salvador Bernal designs the stage and J. Michael Gillette's design process - Tansiongco, Steven G.
The advancement of digital technology has manifested into different aspects of art. One of these art forms is theatre, that has improved its aesthetic creative potential and has paved the way for numerous possibilities of innovating styles and treatments in storytelling, particularly through the use of continuously developing element, video projection. This study has explored the various facets of video projection project in staging the UP Dulaang Laboratoryo's Makinal, Eljay Castro Deldoc's adaptation of Sophie Treadwell's Machinal (1928) through Badong: Salvador Bernal designs The Stage (2014), a collective analysis by Nicanor Tiongson, Gino Gonzales, and Ricardo cruz and the design process included in J. Michael Gillette's Theatrical Design and Production: An Introduction to Scene Design and Construction, Lighting, Sound, Costume, and Make-up (2000). The fundamental factors of video projection design for theatre productions and the application of the given studies on the overall artistic process will be also discussed. This study may serve as a guide for theatre practitioners who aspire to use video projection design in creating the visual world of a play.